A study on Singapore SMEs usage of new business practices in MNCs - Lee, Joy Sihui (2011)
Our study sets out to understand the existing support technologies and structures used by Singapore Small and Medium Enterprises (SMEs) as compared to those used by multinational companies. To investigate this, we carried out secondary research through observations of websites and other sources and primary research through surveys to determine their current structures and support technology. Following that, we analyzed our survey results by presenting them in a graphical form and looked at the companies using their strategy, age, size and industry. In our findings, we note that differences occurred in these different bandings: Industry types were significant in influencing the type of controls and communication tools used by companies e.g. companies in manufacturing industry tend to invest more in logistical controls; smaller companies adopting the focused strategy tend to use advanced financial control; while middle aged companies were most resistant to using newer forms of communication. The study essentially contributes to current literature on Singapore SMEs through providing a snapshot of current MNC business trends popular amongst SMEs. This would add value to businessmen running SMEs as they would be able to implement tools they lack on the industry level or realize ways to further differentiate their operations. Spring Singapore may also find this information useful in aiding SMEs through understanding what they lack in terms of their business operations and industry standards.